Complete Chloroplast Genomes Provide Insights Into Evolution and Phylogeny of Campylotropis (Fabaceae) - Feng, Yu; Gao, Xin-Fen; Zhang, Jun-Yi; Jiang, Li-Sha; Li, Xiong; Deng, Heng-Ning; Liao, Min; Xu, Bo (Frontiers in Plant Science, 2022)
The genus Campylotropis Bunge (Desmodieae, Papilionoideae) comprises about 37 species distributed in temperate and tropical Asia. Despite the great potential in soil conservation, horticulture, and medicine usage, little is known about the evolutionary history and phylogenetic relationships of Campylotropis due to insufficient genetic resources. Here, we present 21 complete chloroplast genomes of Campylotropis species assembled from deep whole-genome resequencing data. In combination with the previously published chloroplast genomes of C. macrocarpa and closely related species, we conducted comparative genomics and phylogenomic analysis on these data. Comparative analysis of the genome size, structure, expansion and contraction of IR boundaries, number of genes, GC content, and pattern of SSRs revealed high similarities among the Campylotropis chloroplast genomes. The activities of long sequence repeats contributed to the variation in genome size and gene content in Campylotropis chloroplast genomes. The Campylotropis chloroplast genomes showed moderate sequence variation, and 14 highly variable regions were identified for further studies of species delimitation, phylogenetic, and population genetic studies. We also reported one more case of matK pseudogene in the legume family. The phylogenetic analysis confirmed the monophyly of Campylotropis and the sister relationship between Lespedeza and Kummerowia, the latter two genera were then sister to Campylotropis. The intrageneric relationships of Campylotropis based on genomic scale data were firstly reported in this study. The two positively selected genes (atpF and rps19) and eight fast-evolving genes identified in this study may help us understand the adaptation of Campylotropis species. Overall, this study enhances our understanding of the chloroplast genome evolution and phylogenetic relationships of Campylotropis.